O PAPEL DA COMUNICAÇÃO FACE A FACE NAS ORGANIZAÇÕES NO CONTEXTO DA SOCIEDADE MIDIATIZADA - MAIO, ANA MARIA DANTAS DE (2016)
This study addresses face-to-face communications in organizations according to different theoretical approaches. It considers the perspective of simultaneous occurrence of different forms of communication, since enterprises use different channels to interact with its various publics of interest. It takes into account the mediatization phenomenon, which restructures the way in which people relate with each other in contemporary society. The general aim of the research is to systematize roles that are potentially played in face-to-face interaction and to determine some of the circumstances that apply to its practice in organizations. Since this is a theoretical dissertation, bibliographical survey stands out as one of its main methodological procedures; analyses of empirical cases and a case study developed at Embrapa Pantanal constitute illustrative instances. The conclusion is that face-to-face communication occurs in enterprises simultaneously and combined with other communication channels, however, allowing practical and philosophical results as of yet scarcely explored. Only seldom is in person contact used strategically as a mechanism for establishing relationships, finding out the reaction of others and adjusting communications accordingly, linking corporate discourse to practice and evaluating the context within which interactions take place, which can be decisive for corporate communication.